Magnetic phase transition in valence tautomers as polymorphs of 3-iodolawsone: Single crystal X-ray structure, DSC and EPR studies - Zaware, Santosh B.; Dagade-Waghmode, Shobha; Gonnade, Rajesh G.; Srinivas, Darbha; Rane, Sandhya Y. (Journal of Molecular Structure, 2009)
Three polymorphs of 3-iodolawsone (I-III) have been isolated and characterized by single crystal X-ray diffraction, electron paramagnetic resonance (EPR) spectroscopy and differential scanning calorimetry (DSC) techniques. Polymorphs I and II were crystallized from methanol in two different valence tautomeric forms: hydroxynaphthoquinone (HNQ) and hydroxynaphthoseimquinone (HNSQ) as needles and thick plates, respectively. Polymorph III was crystallized from ethanol in HNQ form, as thin plates Chiral crystals of I belongs to the orthorhombic P2(1)2(1)2(1) space group: II and III belong to the monochnic non-centrosymmetric space group Cc. The molecules are packed via O-H O bonding and pi . pi stacking interactions. The study reveals that relatively stronger intermolecular H-bonding (2.02 angstrom) and most favoured pi . pi stacking (similar to 3 49 angstrom) interactions lead II to HNSQ radicals, presence of which was confirmed by EPR (g = 2.0052) spectroscopy. Interestingly, these materials exhibit crystal-to-crystal magnetic phase transition from polymorph I (diamagnetic) to polymorph II (paramagnetic structure) at 171.1 degrees C as identified by DSC and X-ray crystallographic studies (C) 2009 Elsevier B.V. All rights reserved
Keywords: 3-Iodolawsone; Hydroxynaphthoquinone (HNQ); Hydroxynaphthosemiquinone radical (HNSQ); Magnetic phase transition; Polymorphs; Valence tautomers